Doing Business in Russia 2012 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Russia 2012 is the second subnational report in the Doing Business series in Russia. In 2009, quantitative indicators on business regulations were published for 10 cities: Irkutsk, Kazan, Moscow, Perm, Petrozavodsk, Rostov-on-Don, Saint Petersburg, Tomsk, Tver, and Voronezh. This year, Doing Business in Russia in 2012 documents improvements in the 10 cities previously measured and expands the analysis to 20 new cities across the nation: Kaliningrad, Kaluga, Kemerovo, Khabarovsk, Kirov, Murmansk, Novosibirsk, Omsk, Samara, Saransk, Stavropol, Surgut, Ulyanovsk, Vladikavkaz, Vladivostok, Volgograd, Vyborg, Yakutsk, Yaroslavl, and Yekaterinburg. Data for Moscow is taken from the annual Doing Business report. The selection criteria include the level of urbanization, population, economic activity, political and geographical diversity, and other factors. The cities were selected by the Ministry of Economic Development of the Russian Federation. Doing Business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 4 stages of the life of a business are measured at the subnational level in Russia: starting a business, dealing with construction permits, getting electricity, and registering property. These indicators were selected because they cover areas of local jurisdiction or practice. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why. The data in Doing Business in Russia 2012 are current as of November 2011.